RETRACTED: An ounce of prevention or a pound of cure? Multi-level modelling on the antecedents of mobile-wallet adoption and the moderating role of e-WoM during COVID-19 - Zamil, Ahmad M. A.; Ali, Saqib; Poulova, Petra; Akbar, Minhas (Frontiers in Psychology, 2022)
During the COVID-19 epidemic, personal safety has received increasing attention, leading to behavioral changes. Mobile-wallet (m-wallet) make it easier for people to keep social distance, which helps stop the spread of the COVID-19 virus. Evolving internet technology has brought about changes in consumer lifestyle. The current situation of Covid-19 has created a business environment to shift from traditional ways and adopt e-commerce solutions worldwide. Grounded in TAM’s theory, this study’s objective is two-fold: First, this study intends to examine perceived susceptibility to COVID19, perceived severity of COVID19, insecurity and discomfort as the predictors of perceived usefulness and perceived ease of use. Second, the current research intends to test the moderating effect of eWOM on the relationship between attitude and usage intention. By using survey methods, 226 usable responses were collected through a mall intercept survey in Pakistan. Data were analyzed by using Partial least square (PLS). The results revealed that perceived ease of use and perceived usefulness positively influence attitude towards M-wallet. This study has found that attitude positively influences usage intention in adopting M-wallet. The results also support the moderating role of e-WOM. These findings contribute to the marketing literature in several ways, particularly in Pakistan. This is the first study to use eWOM as a moderating variable in the TAM theory. In addition, this study adds to the current body of knowledge by considering eWOM as a multi-dimensional construct novel in m-wallet literature.